FACTORS OF KNOWLEDGE ECONOMY AFFECTING ON INCOME INEQUALITY IN POST-SOVIET COUNTRIES (Journal of Economic Research & Business Administration, 2018)
The importance of knowledge in the economy is so remarkable that many economists consider theirrole to be even stronger than traditional production factors such as labor and capital. The significance ofthis issue is a knowledge-based term. Consequently, the identification of the components of the knowledge.This study examines the impact of the components of the knowledge-based economy on incomeinequality in the Post-Soviet countries. Therefore, using the model of panel data, the influence of suchvariables as education, innovation, information and communication technologies (ICT) and institutionalmodes of income inequality was studied. A significant and positive effect was achieved for the componentsof knowledge, the index of institutional economic regimes; positive, but insignificant effect for theindex of innovation and creativity; negative and significant effect on the education index; and a negativeand insignificant effect on ICT in relation to income inequality in the Post-Soviet countries. Moreover,it was found that the relationship between income inequality and per capita income is similar to an invertedU-shape over time.